Variation of Matric Suction as a Function of Gypseous Soil Dry Density - Hussein Karim; Qasim Al-Obaidi; Ali Al-Shamoosi (Engineering and Technology Journal, 2020)
Gypseous soil is one of the most problematic types of collapsible soils which is affected by many geotechnical factors. The most important factors are the effect of loading and wetting and their relation to soil density, especially when the soil at unsaturation condition. Suction pressure is the main criteria in determining the deformation behaviour of unsaturated collapsible soil when these soils distributed in arid or semi-arid region. In this study, disturbed sample of sandy soil of more than 70% gypsum content is taken from Al-Ramadi city western of Iraq. This study interested to investigate the variation of matric suction with the dry density and their effects on deformation of gypseous soil. For this purpose, a soil-model device provided with high accurate Tensiometers and Time Domain Reflectometry sensors in addition to data logger is designed and manufactured. Tensiometer sensor is used to monitor and measure the matric suction, while the Time Domain Reflectometry is used to monitor and measure the volumetric water content in the soil mass. The results of the tests showed that there is a significant effect of soil dry density on the relationship between the matric suction and water content.